Factors Affecting the Intention to Invest in Islamic SRI in Malaysia - Farish, Adleen; Karim, Norzitah; Zaghlol, Azlul Kalilah (Information Management and Business Review, 2023)
Islamic SRI has shown a flourishing expansion over the last three decades. This demonstrates that there will be a significant opportunity to enhance the Islamic SRI in the Islamic Finance sector. Islamic SRI is a type of investment that facilitates the creation of the ecosystem and promotes responsible investing. The study attempts to look at the factors affecting the intention to invest in Islamic SRI. The theoretical framework is built on the Theories of Planned Behavior (TPB) and Theory of Reasoned Action (TRA). Since the study focuses on the desire to engage in Islamic SRI, the theories are expanded to include three more antecedents: environmental and societal concern, knowledge, and religion. Due to the study’s emphasis on Islamic SRI perspectives, these variables ought to be included. According to the multiple regression analysis, four components, namely attitude, subjective norm and environmental and social factors, were revealed to be positively significant on the intention to invest in Islamic SRI. The study employs quantitative research through an online survey questionnaire. The sampling technique for this study is non-probability sampling by applying the convenience sampling technique. Besides, the targeted population of this study is the potential private investors who reside in the states of Kuala Lumpur and Selangor, while the total sample size of the study is 380.